Respuesta :
To answer the question, directly substitute the value given for t to the given function of height.
h = -16t² + 60t + 6
h = (-16)(3 s)² + (60)(3) + 6 = 42
Therefore, the height of the ball after 3 seconds is 42 ft.
h = -16t² + 60t + 6
h = (-16)(3 s)² + (60)(3) + 6 = 42
Therefore, the height of the ball after 3 seconds is 42 ft.
Answer:
The height of the ball when it hits t = 3 seconds will be 42 feet.
Explanation:
The user above me provides a very helpful explanation, so I am only writing this in his/her/their honor for his/her/their work :D
h = -16t² + 60t + 6
h = (-16)(3 s)² + (60)(3) + 6 = 42